The Jews of eighteenth-century Jamaica : a testamentary history of a diaspora in transition - Mirvis, Stanley (Yale University Press, 2020)
"Based on the last wills and testaments composed by Jamaican Jews between 1673 and 1815, Stanley Mirvis explores the social and familial experiences of one of the most critical, yet understudied nodes of an Atlantic Portuguese Jewish trade network. Mirvis examines how Jamaica's Jews put down roots as traders, planters, pen keepers, physicians, fisherman, entertainers, and metalworkers, and reveals how their presence helped shape the colony as much as settlement in the tropical West Indies transformed the lives of the island's Jews. Mirvis's micro-historical study illuminates Jewish involvement in planting and their patterns of slave ownership. He demonstrates how Jews struggled to find a place within the highly racialized hierarchy of Jamaican society, the Jamaican Jewish path to creole identity, the continuity of converso identity among Portuguese Jews, and the relationship between metropole and colony in the Portuguese Jewish Atlantic"--